Identification of Deep Aquifer Depth in Lava Fan Area, Haruman Peak, Malabar Mountains Based on Audio Magnetotelluric Sounding - Harja, Asep; Hanifah, Shofie Dzakia; Rahmawati, Nabilah; Kusuma, Nabila Putri; Junursya, G. M. Lucki (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2025)
Haruman Peak, located in the southern region of the Bandung Basin, is one of the summits of the Malabar Mountains. This mountain range functions as a significant recharge area for the Bandung-Soreang Groundwater Basin, a role supported by its dense vegetation cover, high precipitation, and slopes that facilitate direct runoff into the basin. Previous studies have identified the presence of shallow aquifers in the Haruman Peak area at depths of less than 40 meters. This study aims to investigate the existence of deeper aquifer systems in the Haruman Peak area using the Audio-Magnetotelluric (AMT) method. AMT data were acquired at three measurement points located on the northern side of a suspected fault zone. The inversion of the AMT data yielded one-dimensional (1D) resistivity models that provide insight into the subsurface structure. These models were used to interpret the lithological composition and to delineate potential aquifer zones. The subsurface stratigraphy in the study area is interpreted to consist of soil, Malabar–Tilu Volcanics (Qmt), and the Waringin–Bedil Andesite Formation, also referred to as Old Malabar (Qwb). The results indicate the presence of deep aquifers at measurement points MB-01 and MB-02, at estimated depths of approximately 1,322 meters and 804 meters, respectively. At point MB-03, a shallow aquifer was identified within a soil layer at a depth of less than 100 meters.